10 CREATIVE BUSINESS MYTHS DEBUNKED. Issue 4 (December 2014) - Orme, Greg
<x xml:space="preserve">Abstract</x> Business creativity is shrouded in unhelpful myths. Greg Orme cuts his way through the folklore to enable some clear creative thinking